Southern Baptist Theological Seminary, 1859-2009 - Wills, Gregory A. (Oxford ; New York : Oxford University Press, 2009)
Tracing the history of the seminary from the beginning to the present, Wills shows how its foundational commitment to preserving orthodoxy was implanted in denominational memory in ways that strengthened the denomination's conservatism and limited the seminary's ability to stray from it. --from publisher description.
Boyce's seminary -- Making bricks without straw : war, disruption, and sacrifice -- Modernism's first martyr : Crawford H. Toy and the inspiration controversy -- All things made new : the end of the heroic age -- William H. Whitsitt, academic freedom, and denominational control -- E.Y. Mullins, Southern Seminary, and progressive theology -- Reasserting orthodoxy : Mullins and denominational leadership -- Orthodoxy, historical criticism, and the challenges of a new era -- Duke K. McCall and the struggle for the seminary's direction -- Losing trust : liberalism and the limits of realist diplomacy -- Declaring holy war : Roy L. Honeycutt and popular control -- The conservative takeover -- R. Albert Mohler and the remaking of Southern Seminary.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Southern Baptist Theological Seminary -- History; Conservatism -- Religious aspects -- Southern Baptist Convention -- History; Electronic books